2012
DOI: 10.1073/pnas.1201336109
|View full text |Cite
|
Sign up to set email alerts
|

Structures of dolomite at ultrahigh pressure and their influence on the deep carbon cycle

Abstract: Carbon-bearing solids, fluids, and melts in the Earth's deep interior may play an important role in the long-term carbon cycle. Here we apply synchrotron X-ray single crystal micro-diffraction techniques to identify and characterize the high-pressure polymorphs of dolomite. Dolomite-II, observed above 17 GPa, is triclinic, and its structure is topologically related to CaCO 3 -II. It transforms above 35 GPa to dolomite-III, also triclinic, which features carbon in [3 + 1] coordination at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 35 publications
4
81
2
Order By: Relevance
“…This agrees with the experimental data of Mao et al (2011), who demonstrated, that CaMg(CO 3 ) 2 is stable under lower-mantle conditions at pressures of up to 83 GPa and, possibly, higher, and contrasts earlier data on the decomposing of dolomite into magnesite + aragonite, under lower-mantle P-T conditions (Biellmann et al 1993;Luth 2001;Shirasaka et al 2002). Recent experiments confirm that high-pressure polymorphism in dolomite could stabilize CaMg(CO 3 ) 2 ; this composition transforms at ~17 GPa into 'dolomite-II' (with a monoclinic structure, according to Santillán et al 2003, or an orthorhombic structure, according to Mao et al 2011, or a triclinic structure for Fe-dolomite, according to Merlini et al 2012) and then, at ~35-41 GPa, into 'dolomite-III' (with monoclinic structure, according to Mao et al 2011 or a triclinic structure in the case of Fe-dolomite, according to Merlini et al 2012) .…”
Section: Depth Of Origin Of the Juina Diamond Hosted Carbonatites Ancontrasting
confidence: 41%
“…This agrees with the experimental data of Mao et al (2011), who demonstrated, that CaMg(CO 3 ) 2 is stable under lower-mantle conditions at pressures of up to 83 GPa and, possibly, higher, and contrasts earlier data on the decomposing of dolomite into magnesite + aragonite, under lower-mantle P-T conditions (Biellmann et al 1993;Luth 2001;Shirasaka et al 2002). Recent experiments confirm that high-pressure polymorphism in dolomite could stabilize CaMg(CO 3 ) 2 ; this composition transforms at ~17 GPa into 'dolomite-II' (with a monoclinic structure, according to Santillán et al 2003, or an orthorhombic structure, according to Mao et al 2011, or a triclinic structure for Fe-dolomite, according to Merlini et al 2012) and then, at ~35-41 GPa, into 'dolomite-III' (with monoclinic structure, according to Mao et al 2011 or a triclinic structure in the case of Fe-dolomite, according to Merlini et al 2012) .…”
Section: Depth Of Origin Of the Juina Diamond Hosted Carbonatites Ancontrasting
confidence: 41%
“…Mao et al (2011) reported that dolomite, above 35 GPa, transforms into a highpressure polymorph which does not decompose into a mixture of aragonite and magnesite at high temperature, as it does at lower pressures (Biellmann et al, 1993). The structure of this polymorph, called dolomite-III, was determined on an Fe-rich sample (Merlini et al, 2012a) and it (1971) possesses structural features similar to those of CaCO 3 -III. The polymorphism of carbonates was also investigated theoretically (Oganov et al, 2006(Oganov et al, , 2008(Oganov et al, , 2013.…”
Section: Introductionmentioning
confidence: 94%
“…Dolomite II (triclinic P1) was observed at ambient temperatures and pressures above ~20 GPa (Santillán et al 2003;Mao et al 2011;Merlini et al 2012). A third dolomite phase, Dolomite III, was recently observed in Ca(Mg 0.92 Fe 0.08 )(CO 3 ) 2 by Mao et al (2011) and Ca(Mg 0.6 Fe 0.4 )(CO 3 ) 2 by Merlini et al (2012), by compressing above 35 GPa and laser heating. This dolomite III phase is stable during temperature-quench, allowing Merlini et al to refine a structure (triclinic P1).…”
Section: Introductionmentioning
confidence: 95%